Kartagener syndrome with renal amyloidosis: a case report - Naredi, Mohit; Patira, Nilesh; Dangar, Hiren; Mehta, Urvansh (International Journal of Research in Medical Sciences, 2023)
Kartagener syndrome is a rare disorder caused by defective ciliary function. It is described as a triad of cystic bronchiectasis, chronic sinusitis, and situs invertus. Renal involvement, although uncommon, is reported. The available evidence in literature consists of case reports and series, which describe various patterns of renal involvement. We hereby describe a case of a young female who presented with advanced renal failure and hypertension requiring urgent hemodialysis. On evaluation, she was found to have the classic triad of bronchiectasis, chronic sinusitis, and situs invertus leading to the diagnosis of Kartagener syndrome. On workup for the cause of renal failure, we found membranoproliferative glomerulonephritis due to amyloidosis secondary to bronchiectasis. This is a rare association and only 1 case has been reported in the available literature. There are no consensus guidelines regarding treatment of this condition, due to paucity of available data and because of rarity of the condition. This disease should be reported to augment the available literature.